2017
DOI: 10.1002/iid3.144
|View full text |Cite
|
Sign up to set email alerts
|

Location of tumor affects local and distant immune cell type and number

Abstract: IntroductionTumors comprise heterogeneous populations of cells, including immune infiltrates that polarize during growth and metastasis. Our preclinical studies on breast cancer (BCa) identified functional differences in myeloid‐derived suppressor cells based on tumor microenvironment (TME), prompting variations in host immune response to tumor growth, and dissemination based on tissue type.MethodsIn order to understand if such variations existed among other immune cells, and if such alteration occurs in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…Although subcutaneous tumor models are a useful tool for rapid screening of potential interventions and generation of early mechanistic insights, robust preclinical evaluation of immunotherapeutics targeting HPV + malignancies requires their implantation in their natural mucosal environment (31, 32). As nearly half of oropharyngeal squamous cell carcinomas occur in the tongue (33), we investigated the two most efficacious immunomodulatory antibody combinations from our flank tumor studies (i.e., α4–1BB/αCD40 and α4–1BB/αCTLA-4) with or without HPV peptide vaccination against HPV + mEER tumors orthotopically implanted in the tongue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although subcutaneous tumor models are a useful tool for rapid screening of potential interventions and generation of early mechanistic insights, robust preclinical evaluation of immunotherapeutics targeting HPV + malignancies requires their implantation in their natural mucosal environment (31, 32). As nearly half of oropharyngeal squamous cell carcinomas occur in the tongue (33), we investigated the two most efficacious immunomodulatory antibody combinations from our flank tumor studies (i.e., α4–1BB/αCD40 and α4–1BB/αCTLA-4) with or without HPV peptide vaccination against HPV + mEER tumors orthotopically implanted in the tongue.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that the combination of HPV vaccine with α4–1BB and αCD40 was highly effective for treating mEER tumors implanted subcutaneously but had limited efficacy against tongue tumors. The tumor microenvironment at these two locations may be comprised of distinct spectrums of immune cells and danger signals that may also affect the trafficking as well as functioning of immune cells (31, 32).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular composition of the TME can also vary depending on the tissue of tumor growth. For example, in a murine model of breast cancer, the immune cell profile was compared between 4T1 tumors growing SC or intratibially ( 63 ). FACS analysis in this model revealed differences in the proportions of macrophages, DCs, CD8 + , and CD4 + T cells in the tibia and under the skin of mice with tumors growing at these sites.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, bone marrow and spleen are two major hematopoietic organs 5, 6 . Although various immune cell subsets from these organs are commonly evaluated in studies, there is a lack of strain- and gender-specific benchmarks for each leukocyte cell subtype for these organs in healthy mice 79 .…”
Section: Introductionmentioning
confidence: 99%